Mobilization of Copper Ions From Insoluble Copper Compounds by Methanobactin - Win, Nay Myo; Heimann, Joseph; Hodgson, Shane (My University, 2014)
We followed the mobilization of copper spectrophotometrically in the presence of methanobactin and other known chemical copper binding agents. We find that methanobactin has a very high affinity for both Copper (I) and Copper(II) and can easily extract copper from all of these minerals, in particular Cu(I) minerals (saturation reached in less than 2 hours for Cu(I) minerals). In addition, unlike another Cu(I) chelating compound, BCS, methanobactin can stabilize the normally unstable Cu(I) ion for long periods of time even in the presence of water and oxygen. These data suggest that in areas where these methanotrophic bacteria are common, secreted methanobactin could have a significant impact on soluble copper concentrations and weathering of copper-containing minerals.
Color poster with text, tables, and graphs.
Keywords: Methanobactin; Copper; Posters